2021
DOI: 10.1038/s41419-021-04213-6
|View full text |Cite
|
Sign up to set email alerts
|

ECHS1, an interacting protein of LASP1, induces sphingolipid-metabolism imbalance to promote colorectal cancer progression by regulating ceramide glycosylation

Abstract: Sphingolipid metabolic dysregulation has increasingly been considered to be a drug-resistance mechanism for a variety of tumors. In this study, through an LC–MS assay, LIM and SH3 protein 1 (LASP1) was identified as a sphingolipid-metabolism-involved protein, and short-chain enoyl-CoA hydratase (ECHS1) was identified as a new LASP1-interacting protein through a protein assay in colorectal cancer (CRC). Gain- and loss-of-function analyses demonstrated the stimulatory role played by ECHS1 in CRC cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…On one hand, this interaction induces cell apoptosis by decreasing the mitochondrial membrane potential and reduces the phosphorylation of a serine/threonine protein kinase (Akt). On the other hand, it leads to an increased reactive oxygen species (ROS) production and promotes UDP-glucose ceramide glycosyltransferase which contributes to the alteration of ceramide metabolism[ 24 ]. Furthermore, HBsAg can inhibit jumping translocation breakpoints leading to increased cell motility and decreased apoptosis[ 13 ].…”
Section: Viral Factorsmentioning
confidence: 99%
“…On one hand, this interaction induces cell apoptosis by decreasing the mitochondrial membrane potential and reduces the phosphorylation of a serine/threonine protein kinase (Akt). On the other hand, it leads to an increased reactive oxygen species (ROS) production and promotes UDP-glucose ceramide glycosyltransferase which contributes to the alteration of ceramide metabolism[ 24 ]. Furthermore, HBsAg can inhibit jumping translocation breakpoints leading to increased cell motility and decreased apoptosis[ 13 ].…”
Section: Viral Factorsmentioning
confidence: 99%
“…Enoyl-CoA hydratase 1 (ECHS1) is an enzyme that promotes the glycosylation of ceramide, which is believed to be a key step in chemotherapy resistance. Monitoring this marker may assist in the selection of appropriate patients for chemotherapy [133]. Another marker, N-MYC downstream-regulated gene 1 (NDRG1), a key regulator of a variety of cell growth regulatory processes and signaling pathways, was shown to enhance chemosensitivity by modulating EGFR trafficking in metastatic CRC [134].…”
Section: Differential Gene and Protein Expression In Crcmentioning
confidence: 99%
“… 63 Li et al found by immunoprecipitation assay that highly expressed ECHS1 binds to the tumor-promoting factor LIM and SH3 protein 1, increasing the glycosylation of ceramide, reprogramming sphingolipid metabolism, thus reducing ceramide levels and inducing drug resistance in colorectal cancer (CRC) cells. 55 In summary, ECHS1-mediated reprogramming of lipid metabolism is mainly reflected in both remodeling of fatty acid and sphingolipid metabolism, and the regulation of fatty acid metabolism reprogramming by ECHS1 may have cancer species specificity.…”
Section: The Functions Of Echs1 In Tumorsmentioning
confidence: 99%
“…Li et al found that endogenous overexpression of ECHS1 significantly enhances the metastatic and invasive ability of HCT116 cells. 55 In addition, it has been found in cancers with high expression of ECHS1, such as ovarian cancer, 42 , 75 breast cancer, 38 , 76 and colon cancer, 37 , 77 that cancer cells tend to spread to adipocyte-rich tissues. Which probably since lipids stored in adipocytes can derive large amounts of fatty acids that generate ATP via FAO to facilitate rapid growth and metastasis of cancer cells.…”
Section: The Functions Of Echs1 In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation